Notes on a Hellenistic Milk Pail - Chairetakis, Yannis (Journal of Hellenistic Pottery and Material Culture, 2018)
Thanks to excavations, their findings and related studies, quite significant data on Hellenistic plain pottery has been gathered. Within this framework some unusual plain vessels are also incorporated, and recently Susan Rotroff offered an important identification of such an unusual plain vessel from the Athenian Agora and Kerameikos as a milk pail. In this short text, I want to take the topic a little further, adding some notes on the shape, the name and the function of these vessels.